Voter Turnout in the 2014 European Parliament Election in Poland - Cześnik, Mikołaj; Chwedczuk-Szulc, Karol; Zaremba, Mateusz (Political Preferences, 2014)
European Parliamentary election 2014 were the third elections for countries that joined European Union in 2004, including Poland. As we may observe from the very beginning of the EP's history, elections suffer constant drop in voter turnout, and since 1999 the turnout total for less than 50%. There are many theories explaining this state of affairs, with most notable “second-order elections" and democracy deficit theories. Polish profile of voter turnout in EP elections seems to fit into frameworks of these theories, and is positioned among EU's members with the lowest turnout. What is specific for electoral behaviour in Poland is stability: the turnout and support for political parties seems to stable and even petrified. This assessment seems to be supported by the results of election within past four years, both on aggregate and individual levels of data. Key words: EP elections, voter turnout, electoral behaviour in Poland, petrification of political scene